2022
DOI: 10.3390/jcm11020392
|View full text |Cite
|
Sign up to set email alerts
|

Proactive Management of Intraoperative Hypotension Reduces Biomarkers of Organ Injury and Oxidative Stress during Elective Non-Cardiac Surgery: A Pilot Randomized Controlled Trial

Abstract: Background: Intraoperative hypotension is associated with increased postoperative morbidity and mortality. Methods: We randomly assigned patients undergoing major general surgery to early warning system (EWS) and hemodynamic algorithm (intervention group, n = 20) or standard care (n = 20). The primary outcome was the difference in hypotension (defined as mean arterial pressure < 65 mmHg) and as secondary outcome surrogate markers of organ injury and oxidative stress. Results: The median number of hypotensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…Several studies [ 16 , 28 , 52 76 ] found that IOH was associated with postoperative detrimental outcomes (such as AKI, myocardial injury, and neurocognitive disorders), which is related to the duration and magnitude of hypotension [ 77 ], suggesting that IOH should be avoided perioperatively ( Table 1 ). Based on existing evidence [ 51 , 56 , 58 , 74 , 75 ], intraoperative MAP should be maintained above 65 mmHg in normal adult patients, and in patients with other comorbidities (for example, coronary artery disease and carotid stenosis), the intraoperative MAP must be individualized based on the patient's pathophysiology and clinical situation. For example, the MAP of patients with chronic hypertension should be maintained above 70 mmHg.…”
Section: Intraoperative Bp Control Target and Its Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies [ 16 , 28 , 52 76 ] found that IOH was associated with postoperative detrimental outcomes (such as AKI, myocardial injury, and neurocognitive disorders), which is related to the duration and magnitude of hypotension [ 77 ], suggesting that IOH should be avoided perioperatively ( Table 1 ). Based on existing evidence [ 51 , 56 , 58 , 74 , 75 ], intraoperative MAP should be maintained above 65 mmHg in normal adult patients, and in patients with other comorbidities (for example, coronary artery disease and carotid stenosis), the intraoperative MAP must be individualized based on the patient's pathophysiology and clinical situation. For example, the MAP of patients with chronic hypertension should be maintained above 70 mmHg.…”
Section: Intraoperative Bp Control Target and Its Implicationsmentioning
confidence: 99%
“…Based on this, considering the large proportion of low-risk patients who undergo conventional common surgery, we should weigh the risk-benefit ratio when using expensive noninvasive hemodynamic devices, as it is a valuable tool or a superfluous toy for the right patients [ 105 ]. Fully automated individualized hemodynamic management has broad prospects with advances in computer technology, especially in high-risk patients, as supported by recent studies [ 75 , 106 , 107 ].…”
Section: Individualized Hemodynamic Management In Perioperative Care ...mentioning
confidence: 99%
“…The transfusion volume correlated with the emergence of peri-operative stroke. Considering that the protective biomarker levels were most pronounced at three months, it can be inferred that blood loss and blood pressure fluctuation play a more significant role in peri-operative stroke [ 9 , 12 , 17 , 25 ]. On the other hand, a persistent decline in neuroprotective factors may increase the patients’ vulnerability to delayed CVA.…”
Section: Discussionmentioning
confidence: 99%
“…The progress of their recovery is determined by comorbidities, age, and circumstances relating to surgery [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Cardiac surgery patients may also experience cognitive-related post-surgical effects due to surgery-associated inflammation, peri-operative hypoperfusion, and free radicals creating a neurotoxic environment as evidenced by the peri-operative release of neurofilament light (NF-L) and protein S100 [ 10 , 11 , 12 , 13 ]. Furthermore, the persistence of local post-surgical neuroinflammation compounds neuronal damage and may lead to shrouded neurodegeneration as part of the chronic process of postoperative neurocognitive decline (POCD) [ 9 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…They found lower intraoperative blood loss with the HPI-guided technique. Attempting to answer clinically relevant questions, Morabito et al [ 40 ] hypothesized that treating intraoperative hypotension would result in reduced inflammatory and oxidative stress biomarkers in 40 patients undergoing elective noncardiac surgery. Confirming previous studies, they reported reduced TWA of IOH, number of hypotensive episodes, and time spent in hypotension in the intervention group.…”
Section: Clinical Application Of the Hypotension Prediction Indexmentioning
confidence: 99%